Impact of Agricultural Infrastructure Exposure on Inequality and Social Capital - Andar Ristabet Hesda (Economics Development Analysis Journal, 2022)
Infrastructure is expected as one of the engines of growth. However, there are also concerns about infrastructure externalities, such as inequality, social capital, and environmental issues. This study aims to clarify these unintended consequences of infrastructure, focusing on inequality and social capital. According to the instrumental variable approach, the estimation result shows that the district with high exposure to integrated agricultural infrastructure negatively associates with inequity and positively corresponds to social capital. One of the mechanisms behind it is increased farming productivity. This result implies that the complementarity aspect between infrastructure types should be considered in the infrastructure development plan and execution.